2015
DOI: 10.1073/pnas.1505056112
|View full text |Cite
|
Sign up to set email alerts
|

Loop recognition and copper-mediated disulfide reduction underpin metal site assembly of Cu A in human cytochrome oxidase

Abstract: Maturation of cytochrome oxidases is a complex process requiring assembly of several subunits and adequate uptake of the metal cofactors. Two orthologous Sco proteins (Sco1 and Sco2) are essential for the correct assembly of the dicopper Cu A site in the human oxidase, but their function is not fully understood. Here, we report an in vitro biochemical study that shows that Sco1 is a metallochaperone that selectively transfers Cu(I) ions based on loop recognition, whereas Sco2 is a copper-dependent thiol reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 47 publications
(60 reference statements)
5
86
0
Order By: Relevance
“…According to Leary et al (26), based on studies in cultured human cells, SCO2 and then SCO1 successively transfer a copper ion to COX2, and subsequently SCO2 acts as a thiol-disulfide oxidoreductase for SCO1. However, a recent in vitro biochemical study (31) reported that SCO1 is a metallochaperone that selectively transfers Cu(I) ions based on loop recognition, whereas SCO2 is a copper-dependent thiol reductase of the Cu A cysteine ligands in COX2. Hence, in this scenario, the reduction of the apo-Cu A disulfide by SCO2 Cu(I) is carried out by the metal and not by the thiols.…”
Section: Discussionmentioning
confidence: 99%
“…According to Leary et al (26), based on studies in cultured human cells, SCO2 and then SCO1 successively transfer a copper ion to COX2, and subsequently SCO2 acts as a thiol-disulfide oxidoreductase for SCO1. However, a recent in vitro biochemical study (31) reported that SCO1 is a metallochaperone that selectively transfers Cu(I) ions based on loop recognition, whereas SCO2 is a copper-dependent thiol reductase of the Cu A cysteine ligands in COX2. Hence, in this scenario, the reduction of the apo-Cu A disulfide by SCO2 Cu(I) is carried out by the metal and not by the thiols.…”
Section: Discussionmentioning
confidence: 99%
“…Cu A site formation requires that copper is transferred from COX17 to SCO1, which subsequently catalyzes its insertion into COX2 (9). SCO2 appears to be essential for this latter copper transfer step because it acts as an oxidoreductase on the cysteinyl thiolates of COX2 (15,16).…”
mentioning
confidence: 99%
“…49, 50 SCO1 was originally linked to copper delivery to COX through a high copy suppressor screen of a COX17 null yeast strain. 28 Its copper is coordinated via a Cx 3 C motif and a conserved histidine residue, 5153 and is transferred directly to the Cu A site of COX2 54 in a reaction that also requires the COX assembly factors SCO2 and COA6 (Figure 1). 5558 Interestingly, a multitude of other IMS-localized proteins containing canonical twin Cx 9 C motifs have been implicated in COX assembly in yeast, 59 many of which have evolutionarily conserved mammalian homologues with undefined functions.…”
Section: Copper In Mitochondriamentioning
confidence: 99%
“…45 This led us to propose a model whereby SCO2 acts upon SCO1 to modulate the generation of a mitochondrial signal that regulates the rate of copper efflux from the cell. 23, 45 Subsequent studies demonstrated that SCO2 possesses a thiol-disulphide oxidoreductase activity 54, 56 that may in fact allow it to regulate the generation of a redox signal by targeting the cysteines of the Cx 3 C motif of SCO1. The transduction of this signal at least in part requires COX19, a soluble COX assembly factor which partitions between mitochondria and the cytosol in a copper-dependent manner.…”
Section: Mitochondrial Copper Chaperones Play a Key Role In The Regulmentioning
confidence: 99%